SOBRE EL CUNNILINGUS EN LA ANTIGÜEDAD CLÁSICA SEGÚN F.-K. FORBERG: ANTICIPO DE UNA EDICIÓN ESPAÑOLA DEL MANUAL DE EROTOLOGÍA CLÁSICA (DE FIGURIS VENERIS) - Martos Montiel, Juan Francisco; Salcedo Parrondo, María Cruz (Myrtia, 2002)
This paper offers an edition, with translation and commentaries, of the fifth chapter of F.-K. Forberg's Manual of Classical Erotology , preceeded by a brief presentation of the author and the work and by a reflection on the translation problems that the Latin term cunnilingus may arise.